Monocotylidae (Monogenea) nouveaux parasites de Rhinobatos rhinobatos (Euselachii, Rhinobatidae) - Neifar, L.; Euzet, L.; Ben Hassine, O.K (Zoosystema, 2001)
Two monocotylids, Neoheterocotyle ktarii n. sp. and Calicotyle vicina n. sp. are described, the first one from the gills, the second from the cloaca of Rhinobatos rhinobatos (Linnaeus, 1758) (Elasmobranchii) in Tunisia. N. ktarii n. sp. differs from the cogeners in the morphology of the dorsal sclerites of the haptor and by the size of the penis which is markedly shorter than 75 µm in length. This species is also present in the same host in Senegal. Calicotyle vicina n. sp. resembles C. kroyeri Diesing, 1850 from the cloaca of Raja clavata Linnaeus, 1758 and other species of Raja Linnaeus, 1758. It differs in the morphology of the vaginae in which the ratio of seminal part to the muscular part is 0.42 versus 1.25 in C. kroyeri. Calicotyle vicina n. sp. differs from C. australis Jonhston, 1934 from Rhinobatos typus Bennett, 1830 in the morphology of the penis and vaginae in witch the ratio of seminal part to the muscular part is 0.45 vs 0.85.